Utility of Routine Colonic Biopsies in Pediatric Colonoscopic Polypectomy for Benign Juvenile Hamartomatous Polyps. Issue 4 (April 2017) - Malandra, Michael; Kaur, Sunpreet; Chogle, Ashish
ABSTRACT: Introduction: Benign juvenile hamartomatous polyps are common in pediatric gastrointestinal practice. We hypothesize that in the absence of gross mucosal abnormalities, the likelihood of histologic abnormalities from routine random colonic biopsies is low. Methods: We performed a retrospective chart review identifying patients ages 1 to 18 years who underwent complete colonoscopy and polypectomy for suspected colorectal polyps from January 1, 2004 to July 1, 2014. Indication, age, number of polyps, gross and histologic findings, and any management changes resulting from endoscopy were recorded. Exclusion criteria included history of polyposis syndrome, >5 polyps on colonoscopy, inflammatory bowel disease, and incomplete documentation. Practice patterns were assessed by online survey distributed via Pediatric Gastroenterology listserv. Results: A total of 141 patients underwent colonoscopy with anticipated polypectomy. Seventy-two (63% male) were included. Mean age was 6.5 years. Indication was hematochezia in 71. Findings other than polyps were found in 7 (10%). Juvenile hamartomatous polyps were documented by histologic examination in 68 patients (94%). Routine colonic biopsies were performed in 55 patients (76%). In 8 (15%), histologic abnormalities were seen that did not result in management changes. Seventy-three providers responded to the online survey; 56% reported not taking ileocolonic biopsies in the absence of other mucosal abnormalities; 45% routinely biopsied from the terminal ileum and/or colon. None would biopsy the terminal ileum only. Conclusions: In children with benign juvenile hamartomatous polyps, routine colonic biopsies are not required in the absence of mucosal abnormalities. Overuse of pathology services, increased procedural time, risk, and cost can be avoided.